Effect of preoperative blood lipid levels on the therapeutic efficacy of sigmoid sinus bone wall reconstruction in patients with pulsatile tinnitus caused by sigmoid sinus disease - WU Jing, REN Shaokang, ZHENG Qianyou, ZHU Qiuyang, LI Shenling, ZHANG Xiaowen, FU Tao (精准医学杂志)
Objective To investigate the effect of preoperative blood lipid levels on the therapeutic efficacy of sigmoid sinus bone wall reconstruction in patients with pulsatile tinnitus caused by sigmoid sinus disease. Methods A total of 43 patients with pulsatile tinnitus caused by sigmoid sinus disease who underwent sigmoid sinus bone wall reconstruction in Department of Otorhinolaryngology Head and Neck Surgery in our hospital from May 2019 to September 2022 were enrolled in this study, and accor-ding to the degree of improvement in tinnitus after surgery, they were divided into cured group, response group, and non-response group. Related data were collected and compared between groups, including general information, the serum levels of low-density lipoprotein (LDL), high-density lipoprotein, apolipoprotein A1 (APOA1), apolipoprotein B (APOB), free fatty acid (FFA), triglyceride, and total cholesterol (TC), and APOB/APOA1 ratio before surgery. Results Among the 43 patients, 24 were cured, 14 showed response, and 5 showed no response. The serum levels of LDL, APOB, FFA, and TC and APOB/APOA1 ratio were significantly higher than the normal reference values, while the level of APOA1 was significantly lower than the normal refe-rence value (t=3.683-9.713,P<0.05), and the non-response group had a significantly higher APOB/APOA1 ratio than the ot-her two groups (F=7.527,q=3.120,3.650,P<0.05). Conclusion Sigmoid sinus bone wall reconstruction can effectively alleviate the symptoms of patients with pulsatile tinnitus caused by sigmoid sinus disease, and abnormal blood lipid levels before surgery may compromise the efficacy of surgery by interfering with bone reconstruction. Preoperative evaluation of blood lipid levels, especially APOB/APOA1 ratio, can help to predict surgical outcome, thereby providing efficient treatment for patients.